PROFANITI DALAM FILM 21 JUMP STREET - KATOPPO, VIVI CRISTIANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The title of this study is â€œProfanity in the Movie 21 Jump Streetâ€. The purposes of this study are to identify and classify the kinds of profanity and to find out the kinds of expressions produced by the used of profanity using the theory of Jay (1992) and Staley (1978). This research uses a descriptive method. There are three steps to finish this research, the first step is preparation. In this step, the writer watches the whole movie to find out the data. The second step is data collection. The writer collects the words and compares them with the original script. The third step is data analysis. The writer identifies and classifies the category to find out the types of profanity based onÂ Jayâ€™s (1992) theory and analyzed the expressions based on Staleyâ€™s (1978) theory. The result of this research shows that there are 31 types of profanity from the total number of 42 and 19 kinds of expressions produced according to the context and situation of the dialogues. It also shows that profanity is not only used to express fear or embarrassment, but also to express intimacy and to address compliment and many kinds of expressions. The findings of this research support the theory of Jay and Staley. Key words: Profanity, Types of profanity, Kinds of expressions, Movie: 21 Jump Street, Jay, Staley